REDEVELOPMENT TERMINAL GROGOL 2 SEBAGAI UPAYA EFISIENSI MOBILITAS - Bima K, Fransiskus; Priyono, J.M. Joko (Jurusan Arsitektur dan Perencanaan, 2025)
The increase in vehicle and people mobility at Terminal Grogol 2 has brought several negative impacts on the ongoing operational activities in the terminal. The inability of facilities to accommodate the changes that occur at Terminal Grogol 2 is the main problem in terms of quality, operations and terminal capacity. On the other hand, several phenomena occur in the field that arise due to efforts to meet needs, which in fact affect the formation of new types of users and spaces. Things that are expected to receive good impacts from the changes that will occur at Terminal Grogol 2, including the increasing mobility of vehicles, people, terminal capacity, productivity, facilities, economy and environment. The research method used in achieving maximum data is also a direct survey of the latest conditions of Terminal Grogol 2 which is also compared with journals and articles (trusted sources) to determine the possibility of achieving Terminal Grogol 2 in the future. While in achieving the solution to the problem by making a hypothesis from data to find the relationship between each element in Terminal Grogol 2. Changes are driven by increased efficiency by carrying out the quantity of users of enlarged facilities such as the arrival and departure areas, ticketing, and supporting facilities. Likewise, there are additional facilities related to the relationship with environmental activities, namely an area for street vendors, a space for students to channel their routines, connections with educational facilities and other public transportation located around the terminal and finally an increase in the quality of the Grogol 2 Terminal facilities. Keywords : activity; efficiency; phenomenon; mobility; transportation Abstrak Peningkatan mobilitas kendaraan dan orang pada Terminal Grogol 2 membawa beberapa dampak buruk bagi berlangsungnya kegiatan operasional di dalam terminal. Ketidakmampuan fasilitas dalam menampung perubahan yang terjadi di Terminal Grogol 2 ini yang menjadi masalah utama baik secara kualitas, operasional maupun daya tampung terminal. Disisi lain beberapa fenomena terjadi di lapangan yang timbul karena adanya upaya memenuhi kebutuhan, ternyata mempengaruhi terbentuknya jenis pengguna dan ruang baru. Hal yang diharapkan dapat menerima dampak baik dari perubahan yang akan terjadi di Terminal Grogol 2, diantaranya sejalannya peningkatan mobilitas kenadaraan, orang, daya tampung terminal, produktifitas, fasilitas, ekonomi dan lingkungan. Metode penelitian yang digunakan dalam pencapaian data yang maksimal juga dilakukan survey langsung terhadap kondisi terkirini dari Terminal Grogol 2 yang juga di komparasi dengan jurnal dan artikel (sumber terpercaya) untuk mengetahui kemungkinan pencapaian dari Terminal Grogol 2 ke depannya. Sementara dalam pencapaian solusi permasalahannya dengan melakukan hipotesa dari data untuk mencari hubungan setiap unsur yang ada di Terminal Grogol 2. Perubahan terpacu kepada peningkatan efisiensi dengan melakulan pada kuantitas pengguna fasilitas yang diperbesar seperti area kedatangan keberangkatan, tiketing, dan fasilitas penunjang. Demikian pula adanya penambahan fasliitas terkait hubungan dengan aktivitas lingkungan yaitu area bagi pelaku usaha pedagang kaki lima, ruang bagi mahasiswa untuk menyelurkan rutinitasnya, hubungan dengan fasilitas pendidikan dan transportasi umum lainnya yang berada di sekitar terminal dan yang terakhir peningkatan dari kualitas fasilitas Terminal Grogol 2.